2019
DOI: 10.1177/0300060519869133
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of primary thyroid diffuse large B cell lymphoma and papillary thyroid carcinoma: a case report and literature review

Abstract: Primary thyroid lymphoma (PTL) is a very rare type of thyroid malignant tumor. PTL coexisting with papillary thyroid carcinoma (PTC) is even scarcer and can be easily overlooked. We present our experience of the diagnosis and treatment of a 37-year-old woman with primary thyroid diffuse large B cell lymphoma complicated with PTC. We also considered this case in the context of previous reports. The results indicated that the incidence of concurrent Hashimoto’s disease varied among patients with different lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…A summary of these reports is shown in Table 3. [15][16][17][18][19][20][21][22][23][24][25] Consistent with previous findings, all the 8 patients in our study were female and had papillary thyroid cancers. The phenomenon that these DPM occurs more frequently in women may be related to the fact that thyroid cancer is more common in women than man.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A summary of these reports is shown in Table 3. [15][16][17][18][19][20][21][22][23][24][25] Consistent with previous findings, all the 8 patients in our study were female and had papillary thyroid cancers. The phenomenon that these DPM occurs more frequently in women may be related to the fact that thyroid cancer is more common in women than man.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, rarely has any study to date investigated the association between synchronous thyroid cancer and lymphoma, most of previous reports are case reports. A summary of these reports is shown in Table 3 [15–25] . Consistent with previous findings, all the 8 patients in our study were female and had papillary thyroid cancers.…”
Section: Discussionsupporting
confidence: 88%
“…A study published by Ling Chen et al stated that Hashimoto's thyroiditis was present in 81.25% of patients, which included all patients with mucosa-associated lymphoid tissue (MALT) lymphoma. The study also stated that the incidence of Hashimoto's thyroiditis differed significantly among the four lymphoma groups: MALT, DLBL, MALT + DLBL, and small lymphocytic lymphoma (P=0.014) (11). Although most cases have Hashimoto's thyroiditis in the background, it has been reported that MALT lymphoma can also develop as de novo without the presence of the former (12).…”
Section: Discussionmentioning
confidence: 83%
“…The diagnosis of extranodal marginal zone lymphoma may be delayed due to poor systemic symptoms. The occurrence of B symptoms and cytopenia is very rare in this disease (11,12). Hematological tests along with few additional tests are required for patients with MALT lymphoma that are standard for patients with NHL required at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of PTL from HT, which is rare, usually follows a chronic transformation over many years; however, some cases have been reported in literature to occur within 18 months after the diagnosis of HT [47]. The occurrence of double malignancies, papillary thyroid carcinoma (PTC), and PTL in HT patients is ever rarer, and in literature, only few cases have been reported in the world so far-from China [48][49][50], Italy [51], Korea [52], and Peru [53].…”
mentioning
confidence: 99%